Nutrient synergy in wheat: Impacts of nitrogen and boron on productivity, accumulation, and soil nutrient retention - Prabin Ghimire; Janma Jaya Gairhe; Kishor Kafle; Subodh Khanal (PLoS ONE, 2025)
Efficient nutrient management remains a critical challenge in wheat production, particularly in optimizing productivity while maintaining soil fertility. Among essential nutrients, nitrogen (N) and boron (B) play vital roles in plant growth and grain development, yet their combined effects are not fully understood. To address this gap, a field experiment was conducted from November 2019 to April 2020 in Khairahani, Chitwan, Nepal, to evaluate the effects of different N and B application levels on wheat performance and nutrient retention. The experiment followed a split-plot design, with four N levels (0, 80, 100, and 120 kg ha ⁻ ¹) as main plots and three B levels (0, 1, and 2 kg ha ⁻ ¹) as subplots, replicated three times. Results showed that 120 kg ha ⁻ ¹ of N significantly increased effective tillers (401 m ⁻ ²), 1000-grain weight (52.7 g), spike length (10.05 cm), and spike weight (2.3 g). B applied at 2 kg ha ⁻ ¹ reduced spikelet sterility (34.7%) and increased kernels spike-1 (29.6). The combined application of N and B produced the highest grain yield (6.26 t ha ⁻ ¹) and benefit-cost ratio (2.34). Grain N content (14.48 g kg ⁻ ¹), N uptake (88.5 kg ha ⁻ ¹), and protein content (9.05%) were maximized with 120 kg N ha ⁻ ¹. Likewise, 2 kg B ha ⁻ ¹ significantly improved B content and uptake in both grain and straw. The nutrient treatments had no significant effect on most soil chemical properties, except for residual soil N and B content. These findings indicate that integrating B with N fertilization can substantially enhance wheat productivity and profitability. However, multi-year studies across diverse agro-climatic conditions are necessary to validate these results and develop robust, site-specific nutrient management recommendations.